MANIPULATIVE POTENTIAL OF VOCATIVES IN PEDAGOGICAL DISCOURSE - Katermina, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Forms of vocatives in a speech define a communicative intention of an utterance, indicating a definite addressee. In the process of communication a vocative is a means of creation a special communicative environment consisting of participants of a conversation. By that it defines a line which connects a sender and a recipient of information as well as being a means of the beginning of the communicative process, keeping it up, changing its course either positively or negatively. Vocatives are actively used in a dialogue to attract attention of an interlocutor as well as for further focus of an utterance. It may be used in different manipulative ways (for example, while communicating with a large number of pupils vocatives may serve as a means to draw attention of a recipient or to single out the personality of a pupil). Vocatives in pedagogical discourse may be expressed by proper names and surnames. A vocative with emotional and evaluative suffixes, evaluative adjectives or nouns, possessive pronouns becomes more expressive. They create a more subjective character while qualifying an addressee and by this they become a source of anthropocentricity, representation of a “humane factor” in the language.